2010
DOI: 10.2500/ajra.2010.24.3480
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a Disintegrin and Metalloproteinase 33 Protein in Nasal Polyposis: An Immunohistochemical Study

Abstract: This study suggests that the increased expression of ADAM-33 protein may have a role in the pathogenesis of NP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…Previous researches have shown that ADAMs are active in NPs. An immunohistochemical study has found increased expression of ADAM33 protein in vessels and stroma of NPs tissues ( 39 ). Expression of ADAM8 was higher in NPs tissues than in normal nasal mucosa, and there was a positive correlation between the strength of ADAM8 immunostaining and the level of inflammation in NPs tissues ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous researches have shown that ADAMs are active in NPs. An immunohistochemical study has found increased expression of ADAM33 protein in vessels and stroma of NPs tissues ( 39 ). Expression of ADAM8 was higher in NPs tissues than in normal nasal mucosa, and there was a positive correlation between the strength of ADAM8 immunostaining and the level of inflammation in NPs tissues ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…These patients' case records were reviewed and used to assess the patients' clinical characteristics. 10 This technique allows large numbers of small, punched-out tissue cores from different cases to be analysed in a single immunohistochemical staining experiment. 8 For statistical analysis, TNM classification, clinical stage and tumour differentiation were grouped as follows: T 1 and T 2 tumours versus T 3 and T 4 tumours; clinical stage I and II tumours versus stage III and IV tumours; moderately and poorly differentiated tumours versus well differentiated tumours, and metastatic node negative tumours versus node positive ones.…”
Section: Methodsmentioning
confidence: 99%
“…and silencing of the ADAM33 promoter (14); however, ADAM33 protein has been localized to epithelial cells by immunohistochemistry (17)(18)(19). This might be because a soluble 55-kD protein (sADAM33) is present in the airways, and may bind to epithelial cells; high levels of sADAM33 have been reported in bronchoalveolar lavage fluid of subjects with asthma, and correlated both with disease severity and reduced lung function (20).…”
Section: Clinical Relevancementioning
confidence: 99%